2019
DOI: 10.32734/st.v2i1.347
|View full text |Cite
|
Sign up to set email alerts
|

Pendekatan Chemo-Entrepreneurship Pada Minat Kewirausahaan Siswa SMA N 1 Bukit Perubahan Materi

Abstract: Rendahnya mutu lulusan berakibat pada rendahnya kemampuan kompetitif dan komperatif lulusan. Namun pada kenyataannya banyak siswa SMA yang tidak dapat melanjutkan ke jenjang pendidikan yang lebih tinggi sehingga berpotensi untuk menjadi pengangguran. Dalam penelitian ini untuk meningkatkan minat kewirausahaan dan respon siswa proses pembelajaran kimia perlu adanya suatu inovasi dan pembaharuan dalam suatu pendekatan Chemo-Entrepreneurship (CEP). Kabupaten Bener Meriah merupakan bumi yang subur dan mempunyai be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, students who did not cheat during the pre-test or post-test showed that students do not rely on others and have confidence. Student confidence is also seen from the courage of students to present the results of group discussions without being appointed by the teacher (Ismulyati & Ikhwani, 2018) In Figure 2 it is found that originality gets the highest score, it can be seen from the creativity of students in making products. Creativity is directed to create a new product.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, students who did not cheat during the pre-test or post-test showed that students do not rely on others and have confidence. Student confidence is also seen from the courage of students to present the results of group discussions without being appointed by the teacher (Ismulyati & Ikhwani, 2018) In Figure 2 it is found that originality gets the highest score, it can be seen from the creativity of students in making products. Creativity is directed to create a new product.…”
Section: Resultsmentioning
confidence: 95%
“…Each learning method has advantages and disadvantages. The use of appropriate learning methods and approaches will improve students' abilities and interests in learning chemistry (Ismulyati & Ikhwani, 2019). Students can understand chemical concepts through experience and interaction with the environment.…”
Section: Introductionmentioning
confidence: 99%